ANALYSIS OF DOMESTIC SOLID WASTE MANAGEMENT STRATEGIES IN TUNGA, CHANCHAGA LOCAL GOVERNMENT AREA, NIGER STATE, NIGERIA - FOLORUNSHO, JOSEPH OLANIYI (Advances in Social Sciences Research Journal, 2016)
The management of solid wastes in Nigeria and other African Countries has become a very big challenge, the problem of waste generation, handling and disposal has reached a disturbing level in Nigerian urban centers. The study analyzed domestic solid waste management strategies in Tunga, Niger State, Nigeria which was achieved through characterizing the types of domestic solid wastes generated, examining the domestic solid waste management strategies employed, identifying the key players in domestic solid waste management and ascertaining the effectiveness of the domestic solid waste management strategies employed in the study area. The primary data used in this study was obtained by direct field observations, questionnaire administration and oral interviews while the secondary data was obtained from books, journals, published and unpublished texts, documents, conference articles, government ministries and agencies. 327 out of 2040 households were sampled. The results showed that the nature of domestic solid wastes generated in the study area were mainly organic, paper, plastic, old and rusted metals and textile wastes while the domestic solid waste management strategies in place were burning, open dumping and burying, with open dumping being the most common domestic solid waste management strategy practiced in the study area. It was also observed that the key players involved in the management of solid wastes were the government and individual households and the rate of waste generation was found to exceed the rate of waste disposal in the study area. Also the daily generation of waste (about 74%) exceeded the daily disposal of wastes (about 49%) in the study area. 63% of the respondents reported that burning of domestic solid waste is effective, 84% reported that burying domestic solid wastes is effective while 14% reported that open dumping of domestic solid wastes is effective. The Chi Square analysis showed a significant difference between the frequency of wastes generated and waste disposed in the study area with an alpha value of 0.01, while the Kruskal Wallis H test showed no significant difference in the effectiveness of the domestic solid waste management strategies in the study area (α= 0.646).